2021
DOI: 10.3389/fonc.2021.650292
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor Associated Hepatotoxicity in Primary Liver Cancer Versus Other Cancers: A Systematic Review and Meta‐Analysis

Abstract: BackgroundOverall risks of hepatotoxicity with immune checkpoint inhibitors (ICIs) have yet to be compared in primary liver cancers to other solid tumors.MethodsWe reviewed data from the PubMed, Embase, and Scopus databases, and assessed the risk of hepatotoxicity associated with ICIs.ResultsA total of 117 trials were eligible for the meta‐analysis, including 7 trials with primary liver cancers. The most common hepatotoxicity was ALT elevation (incidence of all grade 5.29%, 95% CI 4.52-6.20) and AST elevation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 144 publications
0
25
0
Order By: Relevance
“…Liver related toxicities are increasingly recognized and with the approval of ICIs for HCC 79 and in patients with underlying liver disease understanding this form of immune mediated hepatotoxicity is of paramount importance. A recent meta-analysis of checkpoint inhibitor studies in HCC demonstrated that the risk of liver injury as measured by liver enzyme elevations (AST and ALT) in patients with HCC is three times higher than other solid tumors 127 . Certain characteristics such as dual ICI therapy, male sex, younger age have been associated with increased risk of hepatotoxicity, however, the reason why certain individuals develop ILICI while others do not, is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Liver related toxicities are increasingly recognized and with the approval of ICIs for HCC 79 and in patients with underlying liver disease understanding this form of immune mediated hepatotoxicity is of paramount importance. A recent meta-analysis of checkpoint inhibitor studies in HCC demonstrated that the risk of liver injury as measured by liver enzyme elevations (AST and ALT) in patients with HCC is three times higher than other solid tumors 127 . Certain characteristics such as dual ICI therapy, male sex, younger age have been associated with increased risk of hepatotoxicity, however, the reason why certain individuals develop ILICI while others do not, is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients experiencing high-grade hepatitis received anti-PD-1 antibodies, but the small sample size does not allow drawing any firm conclusion about safety aspects related to the specific type of antibody. Importantly, it has been reported that anti-PD-1 therapy is associated with a higher risk of hepatotoxicity in comparison with anti-PD-L1 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the incidence of ≥ grade 3 ALT elevation in patients treated with Nivolumab for HCC was 8% in an initial trial (Checkmate 040) ( 28 ), the reported incidence of a similar increase in major trials for lung cancer was 0% ( 29 31 ) and ranged from 0-4% in trials for melanoma ( 32 35 ). In a meta-analysis of 117 trials, the incidence of elevated liver enzymes was increased twofold in patients with liver cancer when compared to other solid tumors overall ( 36 ), higher than in patients treated for melanoma or non-small cell lung cancer ( 6 ). However, this did not lead to an interruption of therapy for HCC patients ( 6 ).…”
Section: Cancer Immunotherapymentioning
confidence: 99%
“…In a meta-analysis of 17 clinical trials, CTLA-4 inhibitors had a higher propensity to cause hepatotoxicity than PD-1 inhibitors (Odds ratio for high-grade hepatoxicity 1.52 vs 0.48) ( 41 ). In a meta-analysis of 117 trials, any-grade ALT and AST elevation was noted in less than 6% of cases and was slightly higher in anti-PD-1 when compared to anti-PD-L1 therapy with ≥ grade 3 increase in 1.3% of cases ( 36 ). In combination therapy, up to a third of patients developed elevated liver enzymes, with ≥ grade 3 hepatitis occurring in 6.4-31% of cases, of which 80% required treatment, representing the most common ≥ grade 3 irAE ( 2 , 3 , 42 ).…”
Section: Cancer Immunotherapymentioning
confidence: 99%